Differences in salivary secretory function between patients with erosive esophagitis and those with nonerosive reflux disease. Issue 4 (26th January 2018) - Manabe, Noriaki; Haruma, Ken; Kusunoki, Hiroaki; Kamada, Tomoari; Hata, Jiro
Abstract: Background and Aim: It has been speculated that impaired salivary flow contributes to abnormal acid clearance in patients with erosive esophagitis (EE). For easy and objective assessment of salivary function, we developed a salivary gland blood flow measurement technique using continuous‐wave Doppler sonography. In the present study, we evaluated the salivary secretory function in patients with EE and those with nonerosive reflux disease (NERD) using this method. Methods: Doppler waveform analysis was performed on the facial artery to assess blood inflow to the submandibular gland of 30 healthy subjects (HS). Blood flow was compared before and after secretory stimulation with 1 mL of lemon juice. Saliva was simultaneously collected and weighed before and after stimulation. Continuous‐wave Doppler sonography was also performed in patients with EE and NERD. The size of the submandibular gland was compared in 26 patients with EE, 41 patients with NERD, and 86 HS. Results: The submandibular gland blood flow increased after stimulation in all HS. Both within‐day and day‐to‐day reproducibility were good. There was a significant correlation between the percent increase in the maximum velocity and the percent increase in salivary secretion. Although the size of the submandibular gland was not significantly different among the three groups, the percent increase in the maximum velocity in patients with EE was significantly smaller than that in HS. Conclusions: We have established an easy method of assessing salivary function in daily practice. This study revealed that a decrease in salivary secretory function is involved in the pathology of EE.